Pengaruh Job Stress dan Lingkungan Kerja Terhadap Kinerja Pegawai Melalui Emotional Exhaustion pada Kantor Wilayah Direktorat Jenderal Pajak Jawa Tengah II - Ifah Latifah; Teguh Krisnata (ProBank, 2025)
This research was conducted with the aim of determining, examining, and This study was conducted with the aim of knowing, testing and analyzing the influence of Job Stress and Work Environment on the performance of employees of the Central Java II Directorate General of Taxes Regional Office with job rotation and Emotional Exhaustion as intervening variables. In this study, 109 respondents were involved as selected samples, representing part of the total population of 151 people. The data analysis methods used in this study include validity, reliability, linearity and hypothesis testing. This study found that job stress significantly affects performance and emotional exhaustion of job rotation, while the work environment has a significant effect on performance but has no significant effect on emotional exhaustion. The performance of employees of the Central Java II Directorate General of Taxes Regional Office is simultaneously influenced by job stress, work environment and emotional exhaustion. The variables of job stress, work environment and emotional exhaustion. together have a contribution of 44.3% of performance variability. Through path analysis, it can be seen that the most dominant path in influencing performance is the direct influence of the work environment variable compared to other paths.